Pengaruh Modernisasi Administrasi Perpajakan, Tax Knowledge, Sanksi Perpajakan Dan Kualitas Pelayanan Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Dynanda Eliza Nadia Loka; Triyono (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study analyzes the effect of tax administration modernization, tax knowledge, tax sanctions, and quality of tax services on individual taxpayer compliance at KP2KP Pacitan. The approach used in this study is a quantitative approach. The population in this study were all individual taxpayers registered at KP2KP Pacitan. The sample was selected using the accidental sampling technique. Data were collected through questionnaires distributed directly or google form and measured using a Likert scale. Data analysis was carried out using multiple linear regression. The results of the study showed that all independent variables, namely tax administration modernization, tax knowledge, tax sanctions, and quality of tax services have a positive and significant effect on individual taxpayer compliance. The limitations of this study are the sampling using the Accidental Sampling technique so that the results of this study cannot be generalized because the samples are not random, and the use of some questionnaires in the form of hard files and some using google forms which can potentially be biased in filling. Further research is recommended to use a more random sample so that the results can be generalized, and can add other variables that may affect individual taxpayer compliance, such as Tax Burden to produce more comprehensive findings.